Differential Patterns of Serum Brain-Derived Neurotrophic Factor Levels in Alcoholic Patients With and Without Delirium Tremens During Acute Withdrawal - Huang, Ming-Chyi; Chen, Chun-Hsin; Liu, Hsing-Cheng; Chen, Chiao-Chicy; Ho, Chia-Chen; Leu, Sy-Jye (Alcoholism, clinical and experimental research, 2011)
Background:  Brain‐derived neurotrophic factor (BDNF) is associated with alcohol addiction and withdrawal‐related neurotoxicity. Delirium tremens (DT) is the most serious complication of alcohol withdrawal syndrome (AWS). In this study, we explored the differences in serum BDNF levels, measured at baseline and 1 week after alcohol withdrawal among alcoholic patients with and without DT. Methods:  Sixty‐five inpatients, fulfilling the DSM‐IV criteria of alcohol dependence and admitted for alcohol detoxification, as well as 39 healthy control subjects were enrolled. The alcoholic patients were divided by the appearance of DTs into the DT group (n = 25) and non‐DT group (n = 40). We collected blood samples of the patient groups on the first and seventh days of alcohol withdrawal and measured serum BDNF levels by sandwich enzyme‐linked immunosorbent assay. Results:  Serum BDNF levels differed significantly among the three groups: (i) control group 14.8 ± 4.7 ng/ml; (ii) non‐DT group 12.3 ± 3.3 ng/ml; (iii) DT group 6.2 ± 2.6 ng/ml (p < 0.001). One week after alcohol withdrawal, the BDNF levels increased significantly for both alcoholic groups. While non‐DT group had comparable BDNF levels (13.4 ± 3.5 ng/ml) with controls, the DT group still exhibited lower levels (8.9 ± 4.4 ng/ml). Conclusions:  This study suggests chronic drinking leads to a reduction in BDNF levels, and patients with more deficient BDNF expression are vulnerable to the development of DTs. Additionally, BDNF levels elevated after prompt alcohol detoxification treatment. These findings indicate that BDNF could involve modifying the phenotypes of AWS as well as the pertinent neuroadaptive processes of alcohol dependence.